'Look on my works ye mighty…': Iconoclasm, education and the fate of statues. Issue 3 (12th September 2021) - Davis, Robert A.
Abstract: In pursuit of an alternative perspective on the so‐called 'statues controversy', this essay brings recent interpretations of the enduring 'power', 'gaze' and 'magic' of statues into alignment with critical histories of iconoclasm, sacred and secular, and New Materialist accounts of our multiple entanglements with the object histories of inherited monuments. Opening with a close reading of Percy Bysshe Shelley's renowned 1818 sonnet, 'Ozymandias', the essay applies the resultant theoretical synthesis to argue for the general restraint of popular iconoclastic and demolitionary acts and largely to caution against the mimetic violence of statue removal in favour of fresh, educative and iconotropic ways of 'making legible', and 're‐reading', statues, pedestals, inscriptions and their diverse contexts past and present.